Partial Substitution of Alfalfa Hay by Stevia (Stevia rebaudiana) Hay Can Improve Lactation Performance, Rumen Fermentation, and Nitrogen Utilization of Dairy Cows - Jiang, Maocheng; Datsomor, Osmond; Cheng, Zhiqiang; Meng, Zitong; Zhan, Kang; Yang, Tianyu; Huang, Yinghao; Yan, Qi; Zhao, Guoqi (Frontiers in Veterinary Science, 2022)
The objective of this study was to determine the effect of replacing on isonitrogenous and isoenergetic basis alfalfa hay with stevia (Stevia rebaudiana) hay in dairy cow diets on nutrient digestion, milk performance, rumen fermentation, and nitrogen (N) utilization. Twenty-four healthy Holstein lactating dairy cattle with similar milk yield 33.70 ± 2.75 (mean ± SD) kg, days in milk 95.98 ± 23.59 (mean ± SD) d, and body weight 587.75±66.97 (mean ± SD) kg were selected and randomly allocated into three groups. The constituents of the three treatments were (1) 30.0% alfalfa hay (AH), and 0% stevia hay (SH) for AH group; (2) 24.0% AH, and 6% SH for 6% SH group; (3) 18.0% AH, and 12% SH for 12% SH group. The substitution of alfalfa hay with stevia hay did not affect dry matter intake (DMI), gross energy (GE) and other nutrients intake but increased the digestibility of neutral detergent fiber (NDF) and acid detergent fiber (ADF). Compared to the AH diet, the cows fed the 6% SH diets had a higher milk yield and concentration of milk fat. Fecal and urinary nitrogen (N) were lower in cows fed 6% SH diet than cows fed AH diet. Milk N secretion and milk N as a percent of N intake were higher in cows fed 6% SH diet than cows fed AH diets. The concentration of ruminal volatile fatty acids, acetic acid and ammonia-N were higher in cows fed 6% SH diet than cows fed AH diet. By comparison, 12% SH group had no effect on milk yield, milk composition, N utilization, and rumen fermentation compared to AH and 6% SH group. In conclusion, it appears that feeding 6% stevia hay, replacing a portion of alfalfa hay, may improve lactation performance and N utilization for lactating dairy cows.